Improving Students’ Speaking Skill Through Probing-Prompting Method at SMA Advent Makassar - Yultri Silamma; Demsi Ronald Claus Matiallo; Suardi Suardi (EDUKASI, 2023)
This research is intended to find out the significant difference of the speaking skill of the second year students at SMA Advent Makassar through Probing-Prompting method. The method of this research is pre- experimental method. This method involved one group that was given pre- test, treatments and post-test.The result of the data analysis shows that there is significant difference between pre-test and post-test by the mean score of post-test (4,15) is greater than the mean score of per-test (2,7) at the level significance 0,05. Based on the findings and discussions, it can be concluded that Probing-Prompting method can improve the students’ speaking skill.